FAKTOR PENYEBAB KETIDAKTEPATAN KODE DIAGNOSIS PADA DOKUMEN REKAM MEDIS RAWAT INAP DI RUMAH SAKIT ISLAM AISYIYAH MALANG - Fakhrur Rozi; Elystia Vidia Marselina (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2022)
One of the competencies of a medical recorder is being able to carry out coding of diseases and actions in accordance with applicable regulations. Errors in determining codes can cause losses to health service facilities. Based on the results of the observations that have been made, it was found that the activity of giving diagnosis codes at Aisyiyah Islamic Hospital still contains errors, namely there is a mismatch between the diagnosis and the diagnosis code. This occurs because the coder is not careful, thus causing errors in coding. The aim of this research is to determine the factors that cause inaccurate diagnosis codes in inpatient medical record documents at the Aisyiyah Islamic Hospital, Malang. This research method uses a qualitative descriptive method. By analyzing the elements that produce inaccuracies in coding based on the man and method elements. This study aims to develop a plan to solve coding errors from patient medical records. Qualitative research was used, with data collection techniques in the form of informant interviews and observational research. Conformity of diagnoses and diagnosis codes at Aisyiyah Islamic Hospital Malang for the 2023 period from a total of 52 samples taken, there were 13.4% incorrect diagnosis codes according to ICD 10 and 86.6% correct diagnosis codes according to ICD 10. The results of the study showed that the cause of inaccuracy in coding Inpatient patient medical record files include unclear doctor's writing, non-standard writing of diagnosis abbreviations, medical record officers are less thorough in coding diagnoses and medical record officers rarely open ICD-10 to ensure the code is accurate or inaccurate.